Analisis Resistensi Spermatozoa Sapi Bali Terhadap Keberhasilan Inseminasi Buatan di Kabupaten Tebo - Fachroerrozi Hoesni; Firmansyah Firmansyah; Farizal Farizal; Fauzan Fauzan (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The purpose of this study is to find out the difference in the success rate of Artificial Insemination of Balinese cattle in Rimbo Bujang Subdistrict, Rimbo Ilir, and to know the influence of spermatozoa resistance and spermatozoa abnormality on the success of Artificial Insemination in Balinese cattle. The method used is the survey method, while the sample withdrawal technique is used clustering. Data analysis uses multiple linear regressions. The results showed that the success of Artificial Insemination based on Service per Conception (S/C) showed the number 1.56 means the success of IB is good, while judging from the calving interval (CI) value in cattle which is 12.9 months, it means it is ideal. It can be concluded that the success of Artificial Insemination (IB) is good, while motility is the success of Artificial Insemination (IB), as well as the percentage of life and spermatozoa abnormalities does not affect the success of Artificial Insemination (IB) in Balinese cows.